The philosophy of wine : a case of truth, beauty and intoxication - Todd, Cain Samuel, 1976- (McGill-Queen's University Press, 2011)
Questions like these have entertained anyone who has ever puzzled over the tasting notes of a wine "expert." Such questions can be bewildering but they also raise fascinating philosophical issues about the nature of sense perception, knowledge, beauty, and meaning. Wine appreciation can reveal important insights about ourselves, our interests, and pleasures. In a lively and engaging discussion of the philosophical significance of wine, Cain Todd brings much-needed clarity to confusions about wine characteristics and the nature of expertise, while championing the objectivity and seriousness of our appreciation of wine. Todd shows that to be able to interpret and appreciate the complexity and unique values of an object that, at first, is just an alcoholic drink, is an incredible thing and an experience without which the world would be a poorer place. Touching on issues in metaphysics, epistemology, and the philosophy of mind, Todd offers a sustained defence of the objectivity of wine judgments, a demystification of the nature of expertise, and a theory of the aesthetic value of wine and its appreciation.